ANALISIS PROSEDUR VOUCHING PADA PENGUJIAN AUDIT ATAS AKUN ASET TETAP (STUDI KASUS DI YAYASAN PENDIDIKAN) - Ahfia Azzahra Agustien; Maulida Salmi Utie; Auliffi Ermian Challen (Media Riset Bisnis Manajemen Akuntansi, 2025)
This case study aims to analyze the audit vouching procedure in testing the assertions of accuracy, cut-off, and completeness of fixed asset accounts at Yayasan ABC (education field). The vouching procedure is carried out to ensure that fixed asset accounts are recorded in accordance with accounting principles by fulfilling the assertions of accuracy, cut-off, and completeness based on all supporting documents. The method used is a descriptive-comparative approach with primary and secondary data obtained. Vouching techniques were applied to all fixed asset addition transactions from 2023 to 2024. The audit results showed that three out of forty six transactions lacked documentation due to human error. The external auditor assessed that the internal control of the Yayasan ABC was sufficiently adequate and found no indication of fraud. Therefore, the externl auditor issued an Unqualified Opinion and provided a management letter to encourage improvements in documentation and internal control. This case study demonstrates that the vouching procedures conducted by external auditor were effective in assessing the reliability of financial information and are important in ensuring compliance with accounting standards.Keywords: vouching, fixed assets, assertions, non government organization